Development of a sexual education package for children from birth to 5 years old, especially for parents, and determining its effectiveness on parents' knowledge, attitude and practice towards preventing sexual abuse and their sense of parenting adequacy - Mortezaei Far, Soudeh; Ebrahimi Qavam, Soghra; Dortaj, Fariborz; Sadipour, Esmaeil; Farokhi, Norali (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The purpose of this study was to design an educational package for sex education for mothers and its effect on knowledge, attitude and practice towards sexual abuse and the feeling of parenting adequacy in the group of normal and single mothers. Method: This research is a fundamental research in terms of compiling a new educational package and an applied research in terms of its application in parent education. Qualitative method is used in package design and quantitative method is used in evaluating the effectiveness depending on the knowledge, attitude and practice and feeling of parenting adequacy. The statistical population of the study for the parents of the two groups, due to the absence of fathers and the impossibility of educating them, mothers were selected for the study. Mothers of normal children, including mothers who refer to kindergartens and care centers in Tehran, and for single-parent children (parent-mother), the statistical population of control mothers have preschool children. First, in order to extract all the important and practical components in the field of sex education, resources and research related to the subject during the last ten years (2010 to 2020) were selected and reviewed. Then, in order to confirm the important and practical components obtained from written sources, the Delphi questionnaire for specialists and experts in the field of child education, in the field of psychology and educational sciences who specialized in the field of sexual education and sexual abuse, and by method Available and snowballs were selected, sent. In order to implement the designed package, first, among normal and control kindergartens in Tehran, mothers with children under 5 years old are selected by available sampling method. The number of samples for each group of mothers of normal children and single parents was 60 people. Which were randomly selected (120 people in total) and were divided into two groups of control and the first and second experiments (30 people in each group). To collect data, Delphi questionnaire, knowledge questionnaire, attitude and practice questionnaire. Parents' response to sexual harassment, parenting adequacy feeling scale was used. In order to analyze the information obtained, the qualitative method and the Delphi questionnaire were used; In this step, standard analysis was used and inferential statistics and multivariate analysis of covariance were used to evaluate the effectiveness of the training package. Results: The results of the study showed that the intervention based on the treatment of child sexual education among mothers, in all components in the experimental group of normal mothers and single parents had an increasing effect on knowledge, attitude, communication performance. The results also showed that there was a significant difference between the pretest and posttest experimental groups and control groups in terms of parental adequacy variable (P